Characterization of electron beam evaporated cdte thin films for optoelectronic devices - El-Raheem, M.M.A.; El-Husainy, N.M.; Ali, Hapipah Mohd (2009)
Thin films of CdTe with different film thickness have been grown on glass substrates with different film thickness by electron beam evaporation technique. The influence of the thickness and annealing temperature on the structural, optical and electrical characteristics of CdTe films have been investigated. The structure of the deposited CdTe films was of the zinc-blend type with a preferential orientation of (111) planes. The optical transmittance of these films was determined using a double beam spectrophotometer. All the spectra reveal interference fringes in the wavelength region from 820 to 2500 nm. The refractive index, n was calculated from the transmission spectra using the Swanepoel's method. The electrical resistivity measurements were carried out using the two-terminal configuration in air. High resistive CdTe films have been obtained after annealing temperature at the temperature 400 degrees C.